2017
DOI: 10.1002/anie.201702352
|View full text |Cite
|
Sign up to set email alerts
|

A Single Spherical Assembly of Protein Amyloid Fibrils Formed by Laser Trapping

Abstract: Protein amyloids have received much attention owing to their correlation with serious diseases and to their promising mechanical and optical properties as future materials. Amyloid formation has been conducted by tuning temperature and chemical conditions, so that its nucleation and the following growth are analyzed as ensemble dynamics. A single spherical assembly of amyloid fibrils of cytochrome c domain‐swapped dimer was successfully generated upon laser trapping. The amyloid fibrillar structure was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…65 Additionally, amyloid fibrils of cyt c are obtained by laser trapping the cyt c 3D-DS dimer, whereas it is relatively difficult to obtain amyloid fibrils from the cyt c monomer. 66 These results show that 3D-DS is useful in constructing various oligomers and assemblies of proteins.…”
Section: D Domain Swappingmentioning
confidence: 78%
“…65 Additionally, amyloid fibrils of cyt c are obtained by laser trapping the cyt c 3D-DS dimer, whereas it is relatively difficult to obtain amyloid fibrils from the cyt c monomer. 66 These results show that 3D-DS is useful in constructing various oligomers and assemblies of proteins.…”
Section: D Domain Swappingmentioning
confidence: 78%
“…65 The decreased stability of the cyt c 3D-DS dimer compared to the monomer has been utilized to construct amyloid fibrils; amyloid fibrils were obtained by laser trapping the cyt c 3D-DS dimer, whereas it was relatively difficult to obtain amyloid fibrils from the monomer. 66 3D-DS cyt c oligomers dissociate to monomers through exothermic processes. 47 The enthalpy change DH of oligomer dissociation is decreased by B20 kcal mol À1 when the oligomer is elongated by one functional (monomer structure) unit.…”
Section: D Domain Swapping Of Native Metalloproteinsmentioning
confidence: 99%
“…It has been reported that domain swapping tends to accelerate aggregation of proteins into amyloid-like fibrils [45,66,92,93]. The domain-swapped cyt c dimer formed a spherical assembly of amyloid fibrils by laser trapping, a method in which molecules are concentrated at the focal point, although amyloid fibrils were difficult to form by laser trapping of the cyt c monomer [94]. It was possible to manipulate spherical assemblies individually in solution to fabricate a threedimensional micro-structure and a line pattern.…”
Section: -2 Domain Swapping and Unique Structural Oligomersmentioning
confidence: 99%